BLU ESTIMATORS AND COMPOSITIONAL DATA - Pawlowsky-Glahn V.; Egozcue Ju.J. (My University, 2002)
One of the principal objections to the logratio approach for the statistical analysis of compositional data has been the absence of unbiasedness and minimum variance properties of some estimators: they seem not to be BLU estimator. Using a geometric approach, we introduce the concept of metric variance and of a compositional unbiased estimator, and we show that the closed geometric mean is a c-BLU estimator (compositional best linear unbiased estimator with respect to the geometry of the simplex) of the center of the distribution of a random composition. Thus, it satisfies analogous properties to the arithmetic mean as a BLU estimator of the expected value in real space. The geometric approach used gives real meaning to the concepts of measure of central tendency and measure of dispersion and opens up a new way of understanding the statistical analysis of compositional data.
Keywords: AITCHISON DISTANCE; CENTERED ESTIMATOR; METRIC VARIANCE; PERTURBATION; SIMPLEX; TERNARY DIAGRAM